2009
DOI: 10.1136/gut.2008.171553
|View full text |Cite
|
Sign up to set email alerts
|

Association of adiponectin multimers with Barrett's oesophagus

Abstract: Objective Barrett’s oesophagus is associated with abdominal obesity. Adiponectin is a peptide that is secreted from adipocytes and circulates in three multimeric forms: low molecular weight (LMW), middle molecular weight (MMW), and high molecular weight (HMW). The anti-inflammatory effects of adiponectin are specific to individual multimers, with LMW being most anti-inflammatory. We postulated that circulating levels of adiponectin and its multimers would be associated with the risk of Barrett’s oesophagus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 42 publications
2
60
2
5
Order By: Relevance
“…A recent epidemiological study by Rubenstein et al indicated that high levels of low-molecular-weight adiponectin were associated with a decreased risk of Barrett's esophagus in patients with GERD [38]. In the present study, no association was found between the total level of adiponectin and the presence of Barrett's esophagus.…”
Section: Discussioncontrasting
confidence: 52%
“…A recent epidemiological study by Rubenstein et al indicated that high levels of low-molecular-weight adiponectin were associated with a decreased risk of Barrett's esophagus in patients with GERD [38]. In the present study, no association was found between the total level of adiponectin and the presence of Barrett's esophagus.…”
Section: Discussioncontrasting
confidence: 52%
“…On the other hand, visceral fat is metabolically active, secreting multiple proinflammatory cytokines such as leptin and adiponectin, which could modulate esophageal inflammation and metaplasia via their proinflammatory actions [58,59]. Actually, it has been reported that higher levels of these cytokines are associated with BE formation [60,61]. Thus, these two adipokines could be involved in the pathogenesis of BE as GERD-independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a case-control study among individuals undergoing oesophagogastroduodenoscopy showed that circulating leptin and proinflammatory cytokines were positively associated with Barrett's oesophagus [38]. In addition, it has been observed that among individuals with GERD symptoms high concentrations of the antiinflammatory low-molecular weight adiponectin are associated with lower risk of Barrett's oesophagus [39]. Findings from another case-control study suggest that blood concentrations of leptin and adiponectin mediate part of the positive association between obesity and risk of Barrett's oesophagus [40].…”
Section: Metabolic Pathwaysmentioning
confidence: 99%